Exploring Collaborative Music Practices in Shaping Social Interaction and Professional Development in Music Education - Kupar N Banurea; Kartini E Simangunsong; Inas Dian P Azizah; Bian Pamungkas; Prisma Tejapermana; Edi Sunjayanto Masykuri (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to explore the role of musical collaboration in fostering social practices within music classrooms and to identify the factors that influence the success of such collaboration. Method: Employing a qualitative approach through interviews and observations, the research investigates how collaboration in music classes contributes to social dynamics among students. The data were collected through interviews conducted in the music studio at Campus A, University of Lampung. Results and Discussion: The findings indicate that collaboration plays a significant role in building team cohesion, enhancing interpersonal skills, and strengthening students’ social character. Collaborative activities, such as arranging songs, vocal and instrumental rehearsals, group discussions to understand music theory, and participation in traditional music practices like the Lampung bronze ensemble, encourage open communication, mutual respect, empathy, and a shared sense of responsibility. Nevertheless, the collaborative process also faces challenges, including differences in individual abilities, varying levels of commitment, and difficulties in unifying creative ideas. Key factors for successful collaboration include effective communication, fair distribution of roles, and a supportive group dynamic. Conclusion: collaboration in music education not only enhances students’ musical competence but also shapes them into cooperative, reflective, and adaptable individuals within both social and professional environments.